2017
DOI: 10.1016/j.adro.2017.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Long-term economic value of hypofractionated prostate radiation: Secondary analysis of a randomized trial

Abstract: PurposeModerately hypofractionated intensity modulated radiation therapy (HIMRT) for prostate cancer shortens the treatment course while providing outcomes comparable with those of conventional intensity modulated radiation therapy (CIMRT). To determine the long-term economic value of HIMRT, including the costs of managing long-term radiation toxicities, a cost minimization analysis compared CIMRT with dose-escalated HIMRT using patient-level data from a randomized trial.Methods and materialsMen with localized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 17 publications
2
18
0
Order By: Relevance
“…Prostate cancer accounts for the longest course of radiation therapy by comparison with other anatomical sites, due to the radioresistant nature of prostatic tissue. International standards suggest that prostate radiation therapy is given as 75.6–81.0 Gy in 1.8–2.0 Gy per fraction over 7–9 weeks . In Australia, typical doses are either 74 Gy (in 37 fractions) or 78 Gy (in 39 fractions) in the setting of post‐prostatectomy or intact prostate respectively.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Prostate cancer accounts for the longest course of radiation therapy by comparison with other anatomical sites, due to the radioresistant nature of prostatic tissue. International standards suggest that prostate radiation therapy is given as 75.6–81.0 Gy in 1.8–2.0 Gy per fraction over 7–9 weeks . In Australia, typical doses are either 74 Gy (in 37 fractions) or 78 Gy (in 39 fractions) in the setting of post‐prostatectomy or intact prostate respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, on cost alone, symptom management represents a small part (<10%) of the average total cost for patients who develop grade 2/3 bowel or urinary toxicity . In contrast, additional studies have demonstrated that hypofractionation is effective in the management of prostate cancer, with attributed health gains …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations